The effect of nutritional status of pregnant women on the incidence of stunting in early childhood - Rika Riyandani; Sriwahyuni; Ria Wahyuni (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: Stunting is a serious public health problem, especially in developing countries, and can long-term impact children's physical and cognitive development. The nutritional status of pregnant women plays an important role in the growth and development of the fetus, which can affect the risk of stunting in children after birth. This study aims to analyze the influence of the nutritional status of pregnant women on the incidence of stunting in early childhood. Research Methodology: This study uses a cohort study design involving pregnant women and their children under five years old. Data were collected through interviews, anthropometric measurements, and laboratory analysis to assess the mother's nutritional status, including macro and micronutrient intake. Result: The analysis showed a significant relationship between the nutritional status of pregnant women and the incidence of stunting in children. Pregnant women with good nutritional status have a lower risk of giving birth to stunted children compared to pregnant women who are malnourished. In addition, factors such as maternal education, economic status, and access to health services also contribute to the incidence of stunting. Conclusion: This study emphasizes the importance of adequate nutrition during pregnancy to prevent stunting in early childhood. Appropriate nutritional interventions and increased awareness of the importance of nutrition during pregnancy are urgently needed to improve maternal and child health. Recommendations for public health programs and nutrition policies were also discussed to address the stunting problem.